The development of the model for recognition of prior learning for nurses in South Africa - T Khanyile (AOSIS, 2005)
The National Qualifications Framework (NQF) was established to address the compartmentalization of education and training, the absence of norms and standards and the need for international recognition. According to the South African Qualifications Authority (1996),this framework was aimed at developing a comprehensive qualifications structure and an integrated approach to education and training in the country (NCHE, 1996:46). Educational institutions, including those for nursing, were challenged with a view to rethink the whole culture of teaching and learning and was counted as knowledge. The major principle of the NQF was the Recognition of Prior Learning (RPL), which had to be pursued across all sectors (Musker, 1998: 8). RPL was seen as a means to widen access into learning programs for those who had been historically denied this. The challenge for educational institutions was how to ensure that RPL systems once implemented did not compromise academic standards. Research into methodologies to implement the NF in the absence of mechanisms was then essential. The purpose of the study was to develop and test a RPL model for nurses in South Africa. The study adopted a multi phase decisions oriented evaluation research design. Stuffelbeam's educational evaluation model was used to guide data collection and analysis. The research questions were incorporated under the different phases of evaluation. The model was development at six levels: level one was at the policy makers level; level two was at the stakeholders; levels three to six were at institutional level where three institutions participated at pilot site for the RPL model development. These levels are presented as tiers in the figure 1. This article present the results of the model development at the first two levels, which according to Stuffelbeam 's model is the context evaluation for boundary setting. Part two will present the model development at institutional level, involving the input and process evaluation and depicted as tiers three, and four.